Antioxidant Defense Mechanisms in Erythrocytes and in the Central Nervous System - Rafael Franco; Gemma Navarro; Eva Martínez-Pinilla (MDPI AG, 2019)
Differential antioxidant action is found upon comparison of organ/tissue systems in the human body. In erythrocytes (red blood cells), which transport oxygen and carbon dioxide through the circulatory system, the most important issue is to keep hemoglobin in a functional state that requires maintaining the haem group in ferrous (Fe2+) state. Conversion of oxidized Fe3+ back into Fe2+ in hemoglobin needs a special mechanism involving a tripeptide glutathione, glucose-6-phosphate dehydrogenase, and glucose and NADPH as suppliers of reducing power. Fava beans are probably a good resource to make the detox innate system more robust as the pro-oxidant molecules in this food likely induce the upregulation of members of such mechanisms. The central nervous system consumes more oxygen than the majority of human tissues, i.e., 20% of the body’s total oxygen consumption and, therefore, it is exposed to a high level of oxidative stress. This fact, together with the progressive age-related decline in the efficiency of the antioxidant defense system, leads to neuronal death and disease. The innate mechanism operating in the central nervous system is not well known and seems different to that of the erythrocytes. The strategies of antioxidant intervention in brain will be reviewed here.